Urban Population Growth and Environmental Sustainability in Nigeria - Edeme, Richardson Kojo; Chibuzo, Nnadi Paschal (Journal of Empirical Studies, 2018)
It is believed that the increasing urban population has led to rapid forest decline and degradation of the environment. This paper examines the impact of urban population growth on environmental sustainability using Nigeria data from 1981-2017. The variables used are urban population growth, fossil fuel consumption, carbon emissions, food production index, arable land, and agricultural raw material exports with renewable energy consumption and forest reserves as explanatory variables. Autoregressive lag model was used to determine the impact of urban population on renewable energy consumption and forest reserves, which are proxies for sustainable environment. From the findings, urban population growth had significant impact on environmental sustainability while real gross domestic product does not have significant impact on renewable energy consumption and forestry. Findings also show that urban population growth increase renewable energy consumption but decrease forest reserves. A basic policy in this direction is effective curtailing in the rate of population growth and depletion of forest reserves.